2020
DOI: 10.1167/iovs.61.4.18
|View full text |Cite
|
Sign up to set email alerts
|

Features of the Choroidal Structures in Myopic Children Based on Image Binarization of Optical Coherence Tomography

Abstract: To evaluate the features of the choroidal structures in the eyes of myopic children obtained by enhanced depth imaging optical coherence tomography (EDI-OCT). METHODS. Ninety-six myopic children with low to moderate myopia (spherical equivalent refractive error [SER],-5.75 to-1.00 diopter) were included in this cross-sectional study. Ocular biometrics were measured using an optical low-coherence reflectometry device. Data of the choroidal structures extracted from a 7500-μm cross-sectional arc of the choroid e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 44 publications
4
31
2
Order By: Relevance
“…The former reflects the circulatory volume in Haller's and Sattler's layers, and the latter reflect areas in the choriocapillaris with low perfusion or without perfusion, thus outlining the global choroidal circulation. These methods have shown good repeatability and reproducibility in studies by others, 32 , 33 , 42 , 44 , 45 as well as by us in the present work.…”
Section: Discussionsupporting
confidence: 77%
“…The former reflects the circulatory volume in Haller's and Sattler's layers, and the latter reflect areas in the choriocapillaris with low perfusion or without perfusion, thus outlining the global choroidal circulation. These methods have shown good repeatability and reproducibility in studies by others, 32 , 33 , 42 , 44 , 45 as well as by us in the present work.…”
Section: Discussionsupporting
confidence: 77%
“…Interestingly, this eccentricity-dependent correlation pattern is the inverse of the ChT and CVI correlation described above. Previous correlation findings appear somewhat inconclusive; low negative correlations of CVI with AEL have been reported, 12 , 18 , 47 while slightly increased vascular components with myopia have also been observed. 20 , 21 However, these findings are all limited to the central or maximally the outer scan fields and do not all reach statistical significance.…”
Section: Discussionmentioning
confidence: 85%
“…This is consistent with earlier studies, although these found generally lower absolute CVI values of around 45% to 65%. 12 , 18 , 47 , 48 These differences likely arise from the use of different OCT devices, scan patterns, image-processing algorithms, and participant age and ethnicity distributions. However, it has been stated that central CVI (measured in two dimensions) is not significantly influenced by the choice of scan pattern 49 or OCT device.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were found in myopic children treated with orthokeratology. 26,27 These findings suggest that the choroidal thickening may participate in ocular growth retardation, probably by influencing the synthesis activity of molecular signals and the transmission ability of choroid, [19][20][21][22] or by increasing the ChT and choroidal blood flow [44][45][46] and mitigating scleral hypoxia. 18 We found that the ChT change at the 1-week visit was negatively associated with the IAL change over 6 months in group A, which suggests that the short-term increase in ChT after a loading dose of 1% atropine may predict longterm eye elongation with weekly treatment.…”
Section: The Changes In Ial and Its Association With Cht Changesmentioning
confidence: 99%